2014
DOI: 10.1038/ncomms4354
|View full text |Cite
|
Sign up to set email alerts
|

NF-Y inactivation causes atypical neurodegeneration characterized by ubiquitin and p62 accumulation and endoplasmic reticulum disorganization

Abstract: Nuclear transcription factor-Y (NF-Y), a key regulator of cell-cycle progression, often loses its activity during differentiation into nonproliferative cells. In contrast, NF-Y is still active in mature, differentiated neurons, although its neuronal significance remains obscure. Here we show that conditional deletion of the subunit NF-YA in postmitotic mouse neurons induces progressive neurodegeneration with distinctive ubiquitin/p62 pathology; these proteins are not incorporated into filamentous inclusion but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 51 publications
4
62
0
Order By: Relevance
“…ChIP-Seq analyses revealed enrichment for NF-Y occupancy near TSSs of annotated genes (Figure 1A), consistent with NF-Y’s preference for binding and recruiting RNA Polymerase II and general TFs to various CCAAT motif-containing promoters (Kabe et al, 2005). Binding of all three subunits to the promoters of known NF-Y targets including Cdc25c , Rnf5 , and Zic3 (Grskovic et al, 2007; Yamanaka et al, 2014) attested to the sensitivity of the ChIP-Seq data (Figure 1B). ChIP followed by quantitative polymerase chain reaction (qPCR) analysis of certain sites, either previously demonstrated as NF-Y bound regions ( Cdc25c , Rnf5 , Zic3 ) or highly enriched for NF-Y binding ( Khsrp ) further validated the quality and the reproducibility of the ChIP-Seq data (Figure 1C).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…ChIP-Seq analyses revealed enrichment for NF-Y occupancy near TSSs of annotated genes (Figure 1A), consistent with NF-Y’s preference for binding and recruiting RNA Polymerase II and general TFs to various CCAAT motif-containing promoters (Kabe et al, 2005). Binding of all three subunits to the promoters of known NF-Y targets including Cdc25c , Rnf5 , and Zic3 (Grskovic et al, 2007; Yamanaka et al, 2014) attested to the sensitivity of the ChIP-Seq data (Figure 1B). ChIP followed by quantitative polymerase chain reaction (qPCR) analysis of certain sites, either previously demonstrated as NF-Y bound regions ( Cdc25c , Rnf5 , Zic3 ) or highly enriched for NF-Y binding ( Khsrp ) further validated the quality and the reproducibility of the ChIP-Seq data (Figure 1C).…”
Section: Resultsmentioning
confidence: 80%
“…While NF-YA heterozygous mice are normal and fertile, NF-YA null mice die prior to 8.5 d.p.c (Bhattacharya et al, 2003), suggesting an essential role for NF-Y in early mouse embryonic development. Interestingly, conditional deletion of NF-YA in postmitotic mouse neurons induces progressive neurodegeneration (Yamanaka et al, 2014), which suggests a role for NF-Y that is independent of its role in cell cycle regulation as has also been shown in hepatocytes (Luo et al, 2011). …”
Section: Introductionmentioning
confidence: 83%
“…Through LIR motif and UBA domain, p62 interacts with ATG8 family and ubiquitinated proteins which is essential for the formation of autophagosomes and degradation of proteins [8]. However, excessive p62 is harmful as shown by the findings that p62 accumulation was associated with neurodegeneration [12, 13], cancer cell proliferation and migration [11] or podocytes epithelial-to-mesenchymal transition [31]. Similarly, in the present work, by using genetic and pharmacological manipulations, we found that p62 accumulation induced by CD38 gene deficiency or lysosomal dysfunction was a major contributor to the proliferation and dedifferentiation change of CAMs.…”
Section: Discussionmentioning
confidence: 99%
“…The p62 mediated selective autophagic clearance of proteins provides an important degradation mechanism, especially when organisms are under the influence of mutation, aging, or environmental stresses [9]. A defect in autophagy may result in an p62 accumulation associated with a host of detrimental effects including rapid tumor growth with adverse prognostic behavior [10], distant metastases [11], neuropathology [12], and neurodegenerative disorders [13]. In the present study, we sought to elucidate whether the p62 accumulation elicited the proliferation and phenotype change of CAMs following autophagy defect induced by CD38 gene deficiency or lysosomal disorder.…”
Section: Introductionmentioning
confidence: 99%
“…NF-Y induces gene expression by bindng to the CCAAT box in the proximal promoter region, so it is also named as the CCAAT binding factor (CBF) (13). It has been known that many genes regulated by NF-Y, so NF-Y plays multiple roles in various contexts, e.g., cell cycle (14), embryonic development (15), endoplasmic reticulum stress (16), fatty acid metabolism, muscle cell differentiation (17), neurodevelopment (18), and so on. …”
Section: Modulation Of Hepatic Nf-y Expression Maymentioning
confidence: 99%